PENERAPAN KINGDOM WORSHIP DALAM PELAYANAN PUJIAN DAN PENYEMBAHAN DI GBI ROCK CITY CENTER, DENPASAR - Gerry, Sean; Limanto, David (STT KINGDOM BALI, 2026)
This study aims to analyze the implementation of Kingdom worship in the praise and worship ministry at GBI ROCK City Center. The research is motivated by the tendency to emphasize intimacy with God in worship practices, while the dimension of reverence and fear of the Lord—an essential component of the culture of the Kingdom of God—receives less attention. This study employs a qualitative research method, involving twelve praise and worship team members as research participants. Data were collected through interviews. The findings reveal that the majority of participants demonstrate a fairly good understanding of Kingdom worship as a natural response of Kingdom citizens to their King, expressed in personal life, communal fellowship, and through the indwelling of the Holy Spirit. Approximately 67% of participants were able to articulate the conceptual meaning accurately, although the emphasis tended to focus more on personal intimacy. Understanding of praise and worship was generally good (75%), particularly regarding the importance of sincere motivation and the awareness of empty worship. In terms of implementation, 83% of participants demonstrated practical expressions of Kingdom worship in daily life, especially through intimacy with God and thanksgiving. Nevertheless, the study indicates that a balanced emphasis between intimacy and reverence toward God still needs to be strengthened. This research concludes that the implementation of Kingdom worship at GBI ROCK City Center is generally very good; however, further theological reinforcement is necessary to ensure a balanced integration between intimacy and reverence in praise and worship ministry practices.